Teaching Psychotherapy to Psychoanalytic Candidates. (December 2018) - Cherry, Sabrina; Rosenberg, Michele; Caligor, Eve
Psychoanalytic institutes have developed a variety of approaches to address the reality that psychoanalytically trained clinicians generally practice more psychodynamic psychotherapy than they do formal psychoanalysis. At the Columbia University Center for Psychoanalytic Training and Research we developed a course for advanced candidates challenging them to integrate what they have learned about doing psychoanalysis during training with their ongoing fund of knowledge about psychotherapy practice. We encourage them to consider how they select treatments and to reflect on similarities and differences between the two modalities with regard to listening, selecting a focus, intervening, and managing the relationship. We also discuss how they approach terminations and how they transition between psychoanalysis and psychotherapy. We selectively use the psychotherapy research literature grounded in the common factors approach in order to update candidates about current knowledge in the field.